2016
DOI: 10.2147/ijn.s95077
|View full text |Cite
|
Sign up to set email alerts
|

Microglial AGE-albumin is critical for neuronal death in Parkinson's disease: a possible implication for theranostics

Abstract: Advanced glycation end products (AGEs) are known to play an important role in the pathogenesis of neurodegenerative diseases, including Parkinson’s disease (PD), by inducing protein aggregation and cross-link, formation of Lewy body, and neuronal death. In this study, we observed that AGE-albumin, the most abundant AGE product in the human PD brain, is synthesized in activated microglial cells and accumulates in the extracellular space. AGE-albumin synthesis in human-activated microglial cells is distinctly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…Advanced glycation end products (AGEs) are potent noxious molecules that induce host cell death and contributing to organ damage. AGEs can induce neurodegenerative diseases [ 60 ] and associate with inflammation and oxidative stress [ 61 , 62 ]. Elevated levels of AGEs ( Fig 4A ) leads to the formations of reactive oxygen and nitrogen species which in turn elicit further AGEs formation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Advanced glycation end products (AGEs) are potent noxious molecules that induce host cell death and contributing to organ damage. AGEs can induce neurodegenerative diseases [ 60 ] and associate with inflammation and oxidative stress [ 61 , 62 ]. Elevated levels of AGEs ( Fig 4A ) leads to the formations of reactive oxygen and nitrogen species which in turn elicit further AGEs formation [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another form of soluble RAGE (sRAGE) (Figure 4) stems from proteolytic cleavage of the native RAGE expressed on the cell surface, both may act as decoys protecting from excessive ligand binding to RAGE and its consequent inflammatory cascades (Leonardis et al, 2012; Raposeiras-Roubín et al, 2010; Vazzana et al, 2009; Yan et al, 2010b). Further, the protective effect of esRAGE against dopaminergic neuronal death through inhibition of AGE-albumin build-up suggests the direct link between AGE-RAGE interaction and neurodegeneration (Bayarsaikhan et al, 2016). …”
Section: Pathways Underlying Age-mediated Effects On Aging and Age-rementioning
confidence: 99%
“…The RAGE interaction with the secreted AGE-albumin complexes has been shown to mediate an apoptotic cascade leading to the death of human dopaminergic neurons. Elevated AGE-albumin accumulation from activated microglia has been suggested as potential biomarkers for neurodegenerative diseases (Bayarsaikhan et al, 2016). Activation of macrophages leads to an exacerbated release of AGE-albumin complexes, a major AGE derivative that drives shared pathways resulting in the progression of neurodegeneration (Byun et al, 2017).…”
Section: Modeling the Influence Of Ages In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Many studies have demonstrated AGEs are considered as potent toxic molecules that produce several non-communicable diseases such as T2D, CRC, cardiovascular diseases, Parkinson disease, AD (63)(64)(65)(66)(67)(68). Epidemiological evidence has reported that elevated AGEs were associated with CRC (69).…”
Section: Ligands Advanced Glycation End-productsmentioning
confidence: 99%